Keteraturan Senam Hamil dengan Tingkat Kecemasan Ibu Hamil Menjelang Persalinan - Surinati I Dewa Ayu Ketut (Jurnal Gema Keperawatan, 2013)
The purpose of this research is to know the relation between pregnant gymnastic regularity with anxiety level towards. The methode of this research was analytic correlation with cross sectional design. Sampling technique used in this research was consekutif sampling by using sample counted 33 responden. Analysis of the data by Spearmen Rank Correlation test. The results of this study indicate that there was a significant relationship between pregnant gymnastic regularity with  anxiety level towards with p value 0,002 and r = 0,256